Threatened powers : when blaming "the Others" grows out of internal instability and protest - Penić, Sandra (Array, 2014)
Once we have established that social and psychological functions of collective outgroup blame vary across contexts, it becomes important to explain the role of contextual factors more precisely. Two central questions are further investigated in this chapter: Under what circumstances are people prone to resent other groups for past wrongdoings? How is out-group blame related to in-group protest? In both cases, the authors propose an argument that completes or qualifies traditional perspectives on intergroup relations and social conflict. These tend to stress the importance of past victimisation. As a complement to this work, the authors show here that adverse societal circumstances can lay the ground for public mobilisation against out groups, even when these conditions are not a direct consequence of past victimisation caused by external enemies. In the first part of the chapter, the authors focus on the context of the new Croatian nation-state. Levels of social and economic deprivation in Croatia range from relatively low to moderate and are largely connected to direct consequences of ethnicised war. Findings show how these structural particularities have created an opportunity to demobilise system critical opposition: higher levels of social and economic deprivation here lead to stronger out-group blame but not to increased internal protest. Lower levels of popularity of the main left-oriented oppositional party in the most deprived areas partially account for this pattern. In the second part of the chapter, analyses are presented that show that, contrary to findings for Croatia, at a larger scale, internal protest is highest within those regions of the whole former Yugoslavia that have endured the highest level of social and economic deprivation. Furthermore, the highest levels of assignment of collective guilt to other groups can similarly be found in the most deprived regions. Furthermore, the individual-level relationship between internal protest and out-group blame varies significantly between contexts: with increasing rates of social and economic deprivation, these two dimensions of political attitudes become increasingly unrelated. These findings provide an illustration of the way in which societal circumstances of system threat can provide both an opportunity to mobilise the public towards domestic reforms and an impetus for elites to mobilise out-group blame.